Ease of Securing Airway Using Bougie Preloaded ProSeal Laryngeal Mask Airway versus Railroading ProSeal Laryngeal Mask Airway Over Bougie - Sunil Rajan; Pulak Tosh; Roniya Ann Roy; Mahesh Madhu; Maneesh Sheela Manikandan; Rejitha Chandrasekharan (Journal of Head & Neck Physicians and Surgeons, 2025)
Background and Aims: First attempt success of ProSeal laryngeal mask airway (PLMA) insertion is low. We compared the number of attempts taken for correct placement of the ProSeal using bougie preloaded PLMA as compared to the railroading of PLMA over a bougie placed in the esophagus. Ease of insertion, time taken for it, incidence of trauma, and hemodynamic responses during the procedure were also compared. Methods: This prospective, randomized study was conducted in 70 surgical patients requiring general anesthesia with PLMA insertion. Following standard intravenous induction, bougie preloaded PLMA was used in Group P, whereas PLMA was railroaded over a bougie placed in the esophagus in Group R. After successful placement of PLMA, glottic structures were visualized and scored with a flexible bronchoscope passed through PLMA. Hemodynamic variables were noted during the procedure. Results: The time taken to secure the airway was significantly shorter in Group P compared to Group R (10.34 ± 6.22 vs. 33.18 ± 8.59 s). First-attempt success was significantly higher in Group R compared with Group P (94.29% vs. 77.14%). Group R had a significantly higher number of easy intubation (88.57% vs. 68.57%). The distribution of fiberoptic view grades was comparable in both groups. Mean arterial pressure was significantly higher in Group P at 1 and 3 min after device placement with comparable heart rates. Conclusion: Railroading of PLMA over bougie placed in the esophagus had a significantly higher first attempt success rate of device placement and was easier compared with bougie preloaded PLMA placement technique. The railroading technique was slower, but without patient desaturation, and resulted in a blunted blood pressure response.